Information blocks coupling of educational information - Касьянов, Володимир Олександрович; Прохоренко, Ірина Володимирівна; Шипитяк, Тетяна Вікторівна (Eastern-European Journal of Enterprise Technologies, 2012)
This paper discusses the problem of information coupling of educational information portions related to the subjects modules content. The problems of assessment of modules disciplines coupling of the curriculum and sequence optimization of educational modules presentation are considered